Pengaruh Video Edukasi tentang Kekerasan Verbal pada Siswa - Iksaruddin, Iksaruddin; Irfan, Ari; Herinawati, Herinawati (Jurnal Akademika Baiturrahim Jambi, 2024)
Verbal violence is violence using harsh words, such as slandering, intimidating, frightening with words, insulting or exaggerating mistakes. In junior and senior high schools, many youths, nearly two out of three, routinely use profanity without realizing the consequences. The purpose of this study was to see the effect of educational videos about verbal violence on students of SMA 7 Jambi City. This type of research is a quantitative study with a pre-experimental design that uses a one group pretest-posttest design without a control group. Measurement of the level of knowledge is carried out before the intervention is given, it will be the initial observation (pretest) after which it will be the last observation (posttest) which allows it to be able to test the changes that occur after the educational intervention about verbal violence packaged in a video via a mobile phone. Data obtained from data processing by univariate analysis and bivariate analysis. The average score for measuring the level of knowledge before being given verbal violence educational videos was 78.61 (95% CI: 62.50-91.25), with a standard deviation of 6,555. The lowest score on this pre-test was 56 while the highest score was 73. Meanwhile, the score the average score for measuring the level of knowledge after being given a verbal abuse educational video was 84.58 (95% CI: 73.75-96.25), with a standard deviation of 4,136. The lowest score on this pre-test was 59 while the highest score was 77. Based on the paired sample test The t-test has a p-value of 0.000 (<0.05), which means that H0 is rejected and Ha is accepted. In conclusion, there is a significant difference between the results of the level of knowledge before and after being given videos of verbal violence at SMA 7 Jambi City